Reduced fetal movements is twin pregnancies and the association with adverse neonatal outcomes. (March 2020) - Levy, Michal; Kovo, Michal; Izaik, Yakira; Ben-Ezry, Emilie; Gonen, Noa; Barda, Giulia; Bar, Jacob; Weiner, Eran
Abstract: Objective: Reduced fetal movements (RFM) is an obstetric complaint known to be associated with adverse neonatal outcomes and should serve as an alarming sign in obstetric triage. Whether this assumption holds for twin pregnancies, is still an obstetric enigma, and this complaint is sometimes overlooked in twins. We, therefore, aimed to study neonatal outcomes in twin pregnancies complicated by RFM. We hypothesised that in twin pregnancy, maternal ability to perceive RFM will be limited, and therefore, will not be associated with adverse neonatal outcome. Study design: Included were all dichorionic twin pregnancies between 2009–2019 who presented to our obstetric triage at a gestational age >34 weeks with an isolated complaint of RFM and delivered during the subsequent two weeks (RFM group). The control group included patients with twin pregnancies (matched for gestational age and maternal age) who presented for routine assessment and reported regular fetal movements throughout pregnancy (no RFM group). Data regarding pregnancy, delivery, and neonatal outcomes were compared between the groups. The primary outcome was a composite of adverse neonatal outcomes, which included one or more of the following: neonatal hypoglycemia, respiratory morbidity, cerebral morbidity, phototherapy, neonatal sepsis, blood transfusions, necrotizing enterocolitis, or neonatal death. Multivariable regression analysis was used to identify independent associations with adverse neonatal outcomes. Results: Maternal demographics and gestational age at delivery did not differ between the RFM group (n = 83 pregnancies and 166 neonates) and the no RFM group (n = 83 pregnancies and 166 neonates). Neonatal birthweights, as well as the rate of birthweights <10th centile, did not differ between the groups. There were 2 cases of fetal demise diagnosed at triage in the RFM group. The rate of the primary outcome, as well as NICU admissions, were significantly higher in the RFM group compared to the no RFM group (29.5 % vs. 19.2 %, p = 0.01 and 32.5 % vs. 19.2 %, p = 0.001). In multivariable analysis RFM (aOR = 1.18, 95 % CI = 1.06–2.73), and GA at delivery (aOR = 0.88, 95 % CI = 0.67-0.97) were associated with adverse neonatal outcome-independent from background confounders. Conclusion: Patients presented to obstetric triage with twin pregnancies and isolated RFM had higher rates of adverse neonatal outcomes and NICU admissions compared to twin pregnancies without RFM.